A high strength-to-toughness aluminum alloy ribbon and method of making using MoAlB refinement and thermomechanical processing
Patent Information
- Application Number
- CN202611249829.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-18
AI Technical Summary
[0005]本发明的目的在于克服现有技术中Al-Cu-Mg系铝合金强度与塑性难以协同提升、晶粒细化剂易中毒、单级轧制组织均匀性差的问题
[0021]通过将MoAlB粉体细化预处理,并经高能球磨实现Al包覆,在熔炼过程中利用铝包覆层改善MoAlB与铝熔体的润湿性;在740~760℃加入复合粉体后,以250~300rpm机械搅拌3~5min,确保了颗粒在熔体中均匀分散,有效避免团聚和沉降;采用先熔化纯铝锭、Al-Cu、Al-Ti、Al-Mn中间合金,后加入Al-Mg中间合金的加料顺序,显著减少了Mg的氧化烧损,保障了合金成分的准确控制;于710~720℃浇铸到200~300℃预热的钢模中,有效预防了铸件开裂。同时,采用固溶、一次冷轧、深冷处理、预时效、二次冷轧与终时效相结合的多级形变热处理工艺;其中,固溶处理(480~500℃,2~3h)使Cu、Mg等合金元素充分固溶;一次冷轧(40%~50%下压率)破碎粗大组织和共晶相,引入位错并积累形变储能;深冷处理(液氮中保温12~15h)利用基体收缩在增强相界面处产生大量热错配位错,促进过饱和固溶体预分解和溶质原子团簇形成;预时效(120~140℃,10~20min)构建高密度、稳定的GP区核心;二次冷轧(40%~60%下压率)引入高密度位错,进一步细化晶粒并对GP区进行应变调控,为终时效创造有利析出条件;终时效(160~170℃,3~6h)在高密度位错和GP区核心协同作用下,促使θ′、S′等强化相均匀弥散析出。上述MoAlB细化与多级形变热处理工艺协同,充分发挥细晶强化、形变强化、位错强化和析出强化的多重作用,突破了传统Al-Cu-Mg系铝合金的强韧性倒置瓶颈,所制备的铝合金带材硬度≥165HV,抗拉强度≥610MPa,屈服强度≥420MPa,延伸率≥8%,微观组织均匀细小,工艺兼容性强,成本可控,在航空航天、轨道交通、汽车轻量化等高载荷结构件领域具有广阔的应用前景。
Smart Images

Figure CN122791234B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of non-ferrous metal alloy technology, specifically relating to a method for preparing high-strength and high-toughness aluminum alloy strips using MoAlB refinement and deformation heat treatment, and the high-strength and high-toughness aluminum alloy material prepared by this method. Background Technology
[0002] Al-Cu-Mg aluminum alloys, due to their high specific strength, good heat resistance, and fatigue performance, have become key materials for load-bearing components in aerospace (such as aircraft frames and rocket shells) and lightweight structural components in automobiles (such as body panels and chassis components). With the increasing demands for lightweighting and reliability in these fields, especially driven by energy conservation, emission reduction, and safety considerations, these alloy strips urgently need to achieve a high strength-toughness balance—that is, possessing both high strength and sufficient ductility to withstand complex loads. However, traditional manufacturing processes often face the dilemma of strength and ductility being mutually restrictive. This is because strengthening mechanisms often sacrifice ductility, making it difficult to obtain excellent comprehensive mechanical properties.
[0003] Currently, the main approaches to improving the strength of Al-Cu-Mg aluminum alloys include grain refinement, strain hardening, and aging precipitation hardening. Grain refinement, in particular, can simultaneously improve strength and plasticity through the Hall-Petch relationship, making it an effective means of optimizing overall performance. Industrially used Al-Ti-B and Al-Ti-C master alloy refiners promote heterogeneous nucleation of α-Al by generating TiB2 or TiC particles. However, these particles easily react with elements such as Cu and Mg at the interface, forming brittle phases or consuming alloying elements, thus reducing refinement efficiency. Simultaneously, TiB2 particles tend to agglomerate and settle, leading to uneven grain size and consequently deteriorating plasticity, especially during continuous casting. In recent years, ternary borides MoAlB have attracted attention due to their good thermal stability and high nucleation efficiency. Their layered structure provides more nucleation sites, but their refinement behavior in aluminum alloys and their synergistic strengthening mechanism with strain heat treatment remain unclear, requiring further research into their interfacial compatibility with the matrix and long-term stability. In terms of deformation strengthening, rolling is the core process in the preparation of aluminum alloy strips, introducing defects through plastic deformation to enhance strength. Conventional room temperature rolling easily leads to severe work hardening and dislocation entanglement, significantly reducing plasticity and potentially causing anisotropy. Cryogenic treatment can utilize the low-temperature shrinkage of the matrix to generate high-density thermally mismatched dislocations at the reinforcing phase interface, and promote the pre-decomposition of supersaturated solid solutions and the formation of solute atom clusters, thus creating favorable conditions for subsequent precipitation control. However, most existing technologies treat cryogenic treatment as an isolated process, lacking process designs that organically integrate it with room temperature pre-deformation, pre-aging, and secondary cold rolling. Furthermore, for alloys that have undergone large deformation and cryogenic treatment, directly applying the traditional T6 aging regime can easily lead to excessively rapid recovery or abnormal grain growth due to the high-energy non-equilibrium state of the microstructure and the presence of numerous defects, resulting in a reversal of strength and plasticity. Although some studies have attempted staged aging or intermediate annealing, the processes are complex and difficult to control, making stable industrial production difficult.
[0004] Existing technologies for preparing high-strength and high-toughness Al-Cu-Mg alloy strips have the following shortcomings: Conventional grain refiners are prone to poisoning and agglomeration in Al-Cu-Mg alloys, limiting their refining effect; single-stage rolling cannot balance strength and plasticity, and the potential of cryogenic treatment has not been systematically synergistic with multi-stage cold rolling and aging; there is a lack of multi-stage deformation heat treatment technology that combines efficient, poison-resistant grain refiners with solution treatment, room temperature cold rolling, cryogenic treatment, pre-aging, secondary cold rolling, and final aging, making it difficult to achieve the optimal balance between grain refinement strengthening, dislocation strengthening, and precipitation strengthening. Therefore, there is an urgent need to develop a process that can synergistically utilize novel refining agents (such as MoAlB) and room temperature-cryogenic dual-stage deformation heat treatment. By optimizing the addition of refining agents, the amount of pre-deformation, the cryogenic deformation temperature, and the heat treatment regime, Al-Cu-Mg aluminum alloy strips with both high strength (≥610MPa) and good plasticity (elongation after fracture ≥8%) can be prepared to meet the demand for highly reliable lightweight structural materials in high-end manufacturing fields (such as next-generation aero-engine components and electric vehicle body structures). Summary of the Invention
[0005] The purpose of this invention is to overcome the problems in the prior art, such as the difficulty in synergistically improving the strength and plasticity of Al-Cu-Mg aluminum alloys, the susceptibility of grain refiners to poisoning, and the poor uniformity of microstructure in single-stage rolling. Instead, it provides a method for preparing high-strength and high-toughness aluminum alloy strips using MoAlB refining and deformation heat treatment.
[0006] The present invention discloses a high-strength and high-toughness aluminum alloy strip, wherein the high-strength and high-toughness aluminum alloy strip is composed of Cu 3.8% to 4.8%, Mg 1.0% to 1.8%, Ti 0.3% to 0.5%, Mn 0.2% to 0.4%, Mo 0.14% to 0.29%, B 0.016% to 0.032%, and the balance being Al and unavoidable impurities by weight.
[0007] This invention discloses a method for preparing high-strength and high-toughness aluminum alloy strips using MoAlB refining and deformation heat treatment:
[0008] S1. MoAlB powder pretreatment: MoAlB powder is dry ball milled to obtain MoAlB powder with a particle size of 2-3 μm.
[0009] S2. Preparation of Al-coated MoAlB composite powder: Take the MoAlB powder obtained in step S1, and dry it with Al powder by wet ball milling to obtain Al-coated MoAlB composite powder.
[0010] S3. Melting and casting: Pure aluminum, Al-Cu alloy, Al-Ti alloy and Al-Mn alloy are melted, refined and slag removed, and then Al-coated MoAlB composite powder obtained in step S2 is added. The mixture is stirred and kept warm. Then Al-Mg master alloy is added and cast to obtain aluminum alloy as-cast billet.
[0011] S4. Deformation heat treatment: The aluminum alloy cast billet obtained in step S3 is subjected to solution treatment, first cold rolling, deep cryogenic treatment, pre-aging, second cold rolling and final aging in sequence to obtain the high strength and toughness aluminum alloy strip.
[0012] Furthermore, in step S1, the dry ball milling uses tungsten carbide balls as the grinding medium, with a ball-to-material mass ratio of (8-10):1, a rotation speed of 250-300 rpm, and a milling time of 10-12 h.
[0013] Further, in step S2, the mass ratio of Al powder to MoAlB powder is (2-4):1, the average particle size of Al powder is 10 μm; the process control agent for wet ball milling is anhydrous ethanol, the grinding medium is steel balls, the rotation speed is 300-350 rpm, and the ball milling time is 8-10 h.
[0014] Further, the smelting and casting described in step S3 specifically involves: melting pure aluminum, Al-Cu alloy, Al-Ti alloy, and Al-Mn alloy at 740–760°C, removing slag, adding Al-coated MoAlB composite powder, and then mechanically stirring for 3–5 minutes while maintaining the temperature. The mechanical stirring speed is 250–300 rpm, and the stirring is carried out for 3–5 minutes. Then, the mixture is cast at 710–720°C into a steel mold preheated to 200–300°C.
[0015] Furthermore, in the Al-coated MoAlB composite powder, the amount of MoAlB added is 0.2% to 0.4% of the total mass of the high-strength and tough aluminum alloy strip.
[0016] Furthermore, the solution treatment temperature in step S4 is 480~500℃, the holding time is 2~3h, followed by water quenching.
[0017] Furthermore, the cold rolling in step S4 is performed in multiple passes, with a total deformation of 40% to 50% and a reduction of ≤10% per pass.
[0018] Furthermore, the cryogenic treatment medium in step S4 is liquid nitrogen, which is kept at a temperature of 12-15 hours and then restored to room temperature.
[0019] Further, in step S4, the pre-aging temperature is 120~140℃, and the temperature is held for 10~20 minutes before water quenching; the secondary cold rolling is a multi-pass room temperature rolling with a reduction rate of 40%~60%; the final aging temperature is 160~170℃, and the temperature is held for 3~6 hours before water quenching.
[0020] The beneficial effects of this invention are:
[0021] By refining and pretreating MoAlB powder and then achieving Al coating through high-energy ball milling, the aluminum coating layer improves the wettability of MoAlB with the aluminum melt during the smelting process. After adding the composite powder at 740–760℃, mechanical stirring at 250–300 rpm for 3–5 minutes ensures uniform dispersion of particles in the melt, effectively preventing agglomeration and sedimentation. The feeding sequence of first melting pure aluminum ingots, Al-Cu, Al-Ti, and Al-Mn master alloys, followed by adding Al-Mg master alloys, significantly reduces Mg oxidation loss and ensures accurate control of alloy composition. Casting at 710–720℃ into a preheated steel mold at 200–300℃ effectively prevents casting cracking. Simultaneously, a multi-stage deformation heat treatment process combining solution treatment, primary cold rolling, cryogenic treatment, pre-aging, secondary cold rolling, and final aging is employed. Solution treatment (480–500℃, 2–3 h) ensures complete dissolution of alloying elements such as Cu and Mg. Primary cold rolling (40%–50% reduction rate) breaks down coarse microstructure and eutectic phase, introducing dislocations and accumulating deformation energy. Cryogenic treatment (holding in liquid nitrogen for 12–15 h) utilizes matrix shrinkage to generate numerous thermally mismatched dislocations at the reinforcing phase interface, promoting the formation of over-strengthened dislocations. Saturated solid solution pre-decomposition and solute atom cluster formation; pre-aging (120-140℃, 10-20min) constructs a high-density, stable GP region core; secondary cold rolling (40%-60% reduction rate) introduces high-density dislocations, further refines the grains and strain-controlled the GP region, creating favorable precipitation conditions for final aging; final aging (160-170℃, 3-6h) promotes the uniform dispersion and precipitation of strengthening phases such as θ′ and S′ under the synergistic effect of high-density dislocations and GP region cores. The aforementioned MoAlB refining and multi-stage deformation heat treatment processes work synergistically to fully leverage the multiple effects of grain refinement strengthening, deformation strengthening, dislocation strengthening, and precipitation strengthening. This breakthrough overcomes the traditional bottleneck of the inverted strength-toughness relationship in Al-Cu-Mg aluminum alloys. The resulting aluminum alloy strip has a hardness ≥165HV, tensile strength ≥610MPa, yield strength ≥420MPa, and elongation ≥8%. It exhibits a uniform and fine microstructure, strong process compatibility, and controllable cost, making it a promising candidate for high-load structural components in aerospace, rail transportation, and automotive lightweighting. Attached Figure Description
[0022] Figure 1 The process flow diagram for preparing high-strength and high-toughness aluminum alloy strips by MoAlB refinement and deformation heat treatment as described in this invention is shown below.
[0023] Figure 2 This is a scanning electron microscope (SEM) image of the Al-coated MoAlB composite powder prepared in Example 1 of this invention.
[0024] Figure 3 These are scanning electron microscope (SEM) images of the microstructure of the cast aluminum alloy before and after MoAlB refinement prepared in Example 2 of this invention.
[0025] Figure 4 The image shows the microstructure of the aluminum alloy prepared in Example 3 of this invention.
[0026] Figure 5 The image shows the microstructure of the aluminum alloy prepared in Example 4 of this invention.
[0027] Figure 6 This is a transmission electron microscope (TEM) image of the aging precipitates in the aluminum alloy prepared in Example 4 of the present invention. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the spirit of the contents disclosed in the present invention will be described in detail below. After understanding the embodiments of the present invention, any person skilled in the art can make changes and modifications based on the technology taught in the present invention without departing from the spirit and scope of the present invention.
[0029] The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0030] The method for preparing high-strength and high-toughness aluminum alloy strips by MoAlB refinement and deformation heat treatment according to embodiments of the present invention will be described in detail below.
[0031] This embodiment provides a method for preparing high-strength and high-toughness aluminum alloy strips using MoAlB refining and deformation heat treatment. The aluminum alloy composition by mass percentage is: Cu 3.8%–4.8%, Mg 1.0%–1.8%, Ti 0.3%–0.5%, Mn 0.2%–0.4%, Mo 0.14%–0.29%, B 0.016%–0.032%, with the balance being Al and unavoidable impurities. Figure 1 The process flow diagram for this high-strength and high-toughness aluminum alloy includes the following steps:
[0032] S1, Pretreatment of MoAlB powder for fine refining:
[0033] MoAlB powder (purity ≥99.9%, initial particle size 10-20 μm) was loaded into a planetary ball mill, and tungsten carbide balls were used as the grinding media. No process control agents were added. The mixture was ball-milled for 10-12 hours at a ball-to-material mass ratio of (8-10):1 and a rotation speed of 250-300 rpm to obtain MoAlB powder with a particle size of 2-3 μm.
[0034] The dry ball milling process described above can effectively reduce the particle size of MoAlB powder without introducing foreign impurities. If the ball milling time is less than 10 hours or the rotation speed is less than 250 rpm, the refining effect is insufficient, resulting in coarse powder particles that are difficult to disperse when subsequently added into the melt. If the ball milling time exceeds 12 hours or the rotation speed is higher than 300 rpm, the powder has already achieved the desired particle size, and further refining with extended time is not significant; excessively high rotation speed will introduce impurities. Therefore, the above ball milling parameters can maintain good powder dispersibility while ensuring a refining effect.
[0035] Preparation of S2 and Al-coated MoAlB composite powder:
[0036] Weigh pure aluminum powder (average particle size 10 μm) and MoAlB powder obtained in step S1 at a mass ratio of (2-4):1, and place them in a ball mill jar; use anhydrous ethanol as the wet milling process control agent and steel balls as the grinding medium, and wet ball mill at a speed of 300-350 rpm for 8-10 hours to obtain a uniform composite slurry; air dry the composite slurry at room temperature to obtain Al-coated MoAlB composite powder.
[0037] During ball milling, finer pure aluminum powder (average particle size 10 μm) undergoes plastic deformation under the impact of steel balls, gradually coating the surface of MoAlB particles to form a uniform Al coating layer. This Al coating layer significantly improves the wettability of MoAlB particles with the aluminum-based melt during subsequent smelting, promoting the uniform dispersion of MoAlB. Controlling the ball milling time to 8–10 hours ensures sufficient and complete surface coating, while avoiding insufficient coating due to too short a milling time, and problems such as severe work hardening of the powder, excessive breakage of MoAlB, or excessive iron impurities introduced by steel ball wear due to excessive milling time.
[0038] S3, Smelting and Casting:
[0039] Pure aluminum ingots, Al-(30~50)Cu, Al-(5~10)Ti, and Al-(5~10)Mn master alloys are melted and stirred evenly at 740~760℃ to ensure that Cu and Mn are fully dissolved and evenly distributed in the melt. A rotating graphite rotor is inserted into the melt, and high-purity argon gas is introduced for rotary spraying refining for 10~15 minutes to remove gas and slag. After that, the slag is removed and the melt is allowed to stand for 5~10 minutes. Then, the Al-coated MoAlB composite powder obtained in step S2 is added. The powder is wrapped in aluminum foil and added to the melt in batches. A mechanical stirrer is started and stirred at a stirring speed of 250~300 rpm for 3~5 minutes to ensure that the composite powder is evenly dispersed in the melt. After stirring, the melt is cooled to 710~720℃, and the Al-(30~50)Mg master alloy is added. After stirring evenly, the melt is allowed to stand for 5~10 minutes. Finally, it is poured into a steel mold preheated to 200-300°C to obtain the cast aluminum alloy.
[0040] It should be noted that if the stirring speed is below 250 rpm, the forced convection is insufficient, making it difficult to evenly disperse the composite powder; if the stirring speed is above 300 rpm, the melt will violently churn, easily leading to air entrapment and accelerated oxidation. Therefore, the above-mentioned stirring speed range ensures both uniform powder dispersion and avoids air entrapment and oxidation. If the mold preheating temperature is below 200℃, the cooling rate is too fast, resulting in excessive internal stress in the cast plate and a tendency to cause cold cracking; if the preheating temperature is above 300℃, the cooling rate is too slow, hindering solidification shrinkage and easily causing thermal cracking. Therefore, the above-mentioned mold preheating temperature range ensures complete filling of the cast plate while effectively preventing cracking.
[0041] S4. Deformation heat treatment:
[0042] The aluminum alloy sheet obtained in step S3 is subjected to the following deformation heat treatment process in sequence:
[0043] (1) Solution treatment: The plate is placed in a heat treatment furnace and heated to 480-500℃ and held for 2-3 hours. Then it is quickly taken out and water quenched. This step allows alloying elements such as Cu and Mg to be fully dissolved into the aluminum matrix to form a supersaturated solid solution, while retaining the uniform structure after homogenization treatment.
[0044] The selection of solution temperature and time is based on the heat treatment characteristics of Al-Cu-Mg aluminum alloys: 480–500℃ ensures sufficient dissolution of the main reinforcing phases and avoids overheating. If the holding time is less than 2 hours, the solution will be insufficient, resulting in insufficient driving force for subsequent aging precipitation and a decrease in peak hardness; if the holding time exceeds 3 hours, the grains are prone to coarsening, and prolonged high-temperature holding may exacerbate the Ostwald ripening of the reinforcing phases, sacrificing the strength-ductility balance of the material.
[0045] (2) First cold rolling: The solution-quenched plate is cold rolled at room temperature with a reduction rate of 40% to 50%. The purpose of this stage is to introduce a certain amount of dislocation and deformation energy storage through cold deformation, to initially refine the solid solution grains, and to prepare the microstructure for subsequent cryogenic treatment.
[0046] When the deformation amount in a single cold rolling process is controlled within 40% to 50%, it is possible to effectively accumulate deformation energy and break down coarse microstructures. If the deformation amount is less than 40%, the introduced dislocation density is too low, limiting the strengthening effect of subsequent cryogenic treatment; if the deformation amount is greater than 50%, the material work hardening intensifies, the risk of edge cracking increases, and excessive energy storage may lead to uneven nucleation of precipitates during subsequent aging.
[0047] (3) Cryogenic treatment: The sheet after one cold rolling is immersed in liquid nitrogen and kept at that temperature for 12-15 hours, and then restored to room temperature. This step causes the aluminum matrix to shrink in an extremely low temperature environment, generating a large number of thermal mismatched dislocations at the interface between the reinforcing phase and the matrix, further increasing the dislocation density; at the same time, cryogenic treatment can promote the pre-decomposition of supersaturated solid solutions, forming uniformly dispersed solute atom clusters, providing nucleation points for pre-aging.
[0048] The above-mentioned effects can be fully achieved when the cryogenic treatment time is controlled between 12 and 15 hours. If the cryogenic time is less than 12 hours, the matrix volume shrinkage is insufficient, the thermal mismatch dislocation multiplication is insufficient, and the solute atom clusters are not formed sufficiently. If the cryogenic time exceeds 15 hours, the energy consumption increases and the performance improvement tends to saturate, which is not economical.
[0049] (4) Pre-aging: After holding at 130℃ for 10-20 min, water quenching is performed. The core of this step is to form a high-density, stable GP zone core at a lower temperature, which provides uniformly dispersed nucleation particles for the final aging precipitation after secondary cold rolling.
[0050] Optimal GP zone density and stability can be obtained when the pre-aging temperature and time are controlled at 120~140℃ and 10~20min. If the time is less than 10min, the number of GP zones will be insufficient, and their guiding effect on the subsequent final aging will be limited; if the time exceeds 20min, the GP zones may grow excessively, reducing the precipitation driving force in the final aging stage and weakening the strengthening effect.
[0051] (5) Secondary cold rolling: The pre-aged sheet is cold rolled at room temperature with a reduction rate of 40% to 60%. This stage aims to introduce high-density dislocations with high deformation to further refine the grains, while causing strain-induced dissolution or shearing of the GP region formed by pre-aging, creating more favorable precipitation conditions for final aging.
[0052] When the deformation amount in the second cold rolling is between 40% and 60%, the optimal synergistic effect of deformation strengthening and precipitation strengthening can be obtained. If the deformation amount is less than 40%, the dislocation density is insufficient, the final aging strengthening effect is limited, and the yield strength of the alloy is difficult to reach above 480 MPa. If the deformation amount is greater than 60%, the material undergoes severe work hardening, the internal stress is too high, and microcracks are easily generated during the rolling process. It may also excessively destroy the GP zone structure formed by pre-aging, resulting in uneven precipitation during final aging and a significant decrease in plasticity.
[0053] (6) Final aging: After holding at 160~170℃ for 3~6h, water quenching is performed to obtain the high-strength and tough aluminum alloy strip. In this step, the supersaturated solid solution decomposes into fine and dispersed aging strengthening phases under the synergistic effect of high-density dislocations and GP zone cores, achieving a significant precipitation strengthening effect.
[0054] The optimal combination of strength and plasticity can be obtained when the final aging time is controlled between 3 and 6 hours. If the aging time is less than 3 hours, the volume fraction of precipitated phase is insufficient, resulting in inadequate strengthening; if the aging time exceeds 6 hours, the precipitated phase becomes significantly coarser, the strength decreases, and there is no additional plasticity gain. Rapid water quenching after final aging can effectively suppress further precipitation during the cooling process, locking the strengthening phase in its optimal size and distribution.
[0055] It should be noted that the ball milling, stirring, smelting, casting, rolling, solution treatment, cryogenic treatment, and aging operations described in the embodiments of the present invention can all be performed using conventional equipment and process parameters in the field of metal processing. For example, smelting is carried out in a resistance furnace, stirring is performed using a mechanical stirrer, rolling is completed on an experimental rolling mill, solution treatment and aging are performed in an air-circulating heat treatment furnace, and cryogenic treatment is carried out in a liquid nitrogen container.
[0056] The features and performance of the present invention will be further described in detail below with reference to specific embodiments.
[0057] Example 1:
[0058] This embodiment provides a high-strength and high-toughness aluminum alloy strip with the following alloy composition (mass fraction): Cu 4.5%, Mg 1.5%, Ti 0.3%, Mn 0.2%, Mo 0.29%, B 0.032%, and the balance being Al and unavoidable impurities.
[0059] This embodiment also provides a method for preparing the high-strength and high-toughness aluminum alloy strip: MoAlB powder (purity ≥99.9%, initial average particle size 15μm) is loaded into a planetary ball mill and dry-milled for 11 hours at a ball-to-powder mass ratio of 9:1 and a rotation speed of 260 rpm using tungsten carbide balls as the grinding medium to obtain MoAlB powder with an average particle size of about 2.5μm; pure aluminum powder with an average particle size of 10μm is weighed at a mass ratio of 3:1 and mixed with the above-mentioned refined MoAlB powder, and wet-milled at a rotation speed of 320 rpm for 8 hours using anhydrous ethanol as the process control agent and steel balls as the grinding medium to obtain a uniform composite slurry, which is then air-dried at room temperature to obtain Al-coated MoAlB composite powder; pure aluminum ingots, Al-50Cu, Al-5Ti and Al-5Mn master alloys are melted at 750℃ and stirred evenly, and then added to the melt. A rotating graphite rotor was inserted, and high-purity argon gas was introduced for rotary spraying refining for 12 minutes to remove gas and slag. After removing the slag, the mixture was allowed to stand for 8 minutes. Then, the obtained Al-coated MoAlB composite powder was wrapped in aluminum foil and added to the melt in batches. A mechanical stirrer was started and stirred at 280 rpm for 4 minutes. After stirring, the melt was cooled to 720°C, Al-50Mg master alloy was added, and the mixture was stirred evenly and allowed to stand for 8 minutes. Finally, the mixture was poured into a steel mold preheated to 250°C to obtain a slab. The deformation heat treatment process was as follows: solution heat treatment at 490°C for 2.5 hours, followed by water quenching, cold rolling at room temperature with a reduction rate of 40%, deep cryogenic treatment with liquid nitrogen for 12 hours, followed by recovery to room temperature, pre-aging at 130°C for 15 minutes, water quenching, secondary cold rolling with a reduction rate of 50%, and finally final aging at 165°C for 5 hours, followed by water quenching to obtain a high-strength and high-toughness aluminum alloy strip.
[0060] Figure 2 The image shows the scanning electron microscope (SEM) morphology of the Al-coated MoAlB composite powder prepared in this embodiment. It can be seen that the pure aluminum powder undergoes plastic deformation and coats the surface of the MoAlB particles. The aluminum alloy obtained in this embodiment was tested for its mechanical properties at room temperature. The results showed a hardness of 172 HV, a tensile strength of 632 MPa, a yield strength of 428 MPa, and an elongation after fracture of 8.5%.
[0061] Example 2:
[0062] This embodiment provides a high-strength and high-toughness aluminum alloy strip with the following alloy composition (mass fraction): Cu 4.2%, Mg 1.3%, Ti 0.4%, Mn 0.2%, Mo 0.22%, B 0.024%, and the balance being Al and unavoidable impurities.
[0063] The difference between the preparation method provided in this embodiment and that in Embodiment 1 lies in the deformation heat treatment process: the first cold rolling reduction rate is adjusted to 45%, the deep cryogenic treatment time is adjusted to 13h, the pre-aging is held at 130℃ for 10min, the second cold rolling reduction rate is adjusted to 40%, and the final aging is held at 165℃ for 6h; the remaining steps are the same as in Embodiment 1.
[0064] Figure 3 The images show scanning electron microscope (SEM) images of the microstructure of the cast aluminum alloy before and after MoAlB refinement, prepared in this example. As can be seen from the images, the addition of MoAlB significantly refines the matrix grains. The aluminum alloy obtained in this example underwent room temperature mechanical property testing, revealing a hardness of 167 HV, a tensile strength of 623 MPa, a yield strength of 426 MPa, and an elongation after fracture of 9.3%.
[0065] Example 3:
[0066] This embodiment provides a high-strength and high-toughness aluminum alloy strip with the following alloy composition (mass fraction): Cu 4.8%, Mg 1.8%, Ti 0.5%, Mn 0.3%, Mo 0.22%, B 0.024%, with the balance being Al and unavoidable impurities.
[0067] The preparation method provided in this embodiment differs from that in Example 1 in that: the MoAlB powder is refined by ball milling at 300 rpm for 10 hours to obtain MoAlB powder with an average particle size of 2.3 μm; in the preparation of the composite powder, the mass ratio of pure aluminum powder to MoAlB is 4:1, and the wet ball milling speed is 350 rpm for 10 hours; the melting temperature is 760℃, the rotary jet refining is performed for 15 minutes, the composite powder is added and stirred at 300 rpm for 3 minutes, the temperature is lowered to 720℃ and Al-30Mg is added, and the steel mold is preheated to 300℃; in the deformation heat treatment, the solution temperature is 490℃ and held for 2 hours, the first cold rolling reduction rate is 50%, the deep cryogenic treatment is performed for 15 hours, the pre-aging is performed at 130℃ and held for 20 minutes, the second cold rolling reduction rate is 60%, and the final aging is performed at 165℃ and held for 4 hours; the remaining steps are the same as in Example 1.
[0068] The microstructure of the aluminum alloy after deformation heat treatment is shown in the image below. Figure 4 As shown, the aluminum matrix grains are significantly elongated along the rolling direction, forming a fibrous deformed structure. The aluminum alloy obtained in this embodiment was tested for room temperature mechanical properties, and its hardness was 179 HV, tensile strength was 668 MPa, yield strength was 462 MPa, and elongation after fracture was 8.0%.
[0069] Example 4:
[0070] This embodiment provides a high-strength and high-toughness aluminum alloy strip with the following alloy composition (mass fraction): Cu 3.8%, Mg 1.0%, Ti 0.3%, Mn 0.2%, Mo 0.14%, B 0.016%, with the balance being Al and unavoidable impurities.
[0071] The preparation method provided in this embodiment differs from that in Example 1 in that: the MoAlB powder is refined by ball milling at 250 rpm for 12 hours to obtain MoAlB powder with an average particle size of 2.6 μm; in the preparation of the composite powder, the mass ratio of pure aluminum powder to MoAlB is 2:1, and the wet ball milling speed is 300 rpm for 8 hours; the melting temperature is 740℃, the rotary jet refining is performed for 10 minutes, the composite powder is added and stirred at 250 rpm for 5 minutes, the temperature is lowered to 710℃ and Al-50Mg master alloy is added, and the steel mold is preheated to 200℃; in the deformation heat treatment, the solution temperature is 490℃ and held for 3 hours, the first cold rolling reduction rate is 40%, the deep cryogenic treatment is performed for 12 hours, the pre-aging is performed at 130℃ and held for 15 minutes, the second cold rolling reduction rate is 40%, and the final aging is performed at 165℃ and held for 3 hours; the remaining steps are the same as in Example 1.
[0072] Micrograph of the aluminum alloy after deformation heat treatment is shown below. Figure 5 As shown, the aluminum matrix grains exhibit a fibrous deformation structure along the rolling direction. Figure 6 The image shows a transmission electron microscope (TEM) image of the aged precipitates in the aluminum alloy prepared in this embodiment, revealing the presence of nanoscale precipitates within the matrix. The aluminum alloy obtained in this embodiment was tested for its mechanical properties at room temperature, showing a hardness of 165 HV, a tensile strength of 612 MPa, a yield strength of 420 MPa, and an elongation after fracture of 9.8%.
[0073] This invention combines MoAlB powder refinement with a multi-stage deformation heat treatment process to fully leverage the synergistic effects of multiple mechanisms, including grain refinement strengthening, deformation strengthening, dislocation strengthening, and precipitation strengthening. This effectively refines the grains, increases dislocation density, and optimizes the distribution of aging precipitates. The aluminum alloy strip prepared within the composition and process range of this invention exhibits a hardness ≥165HV, tensile strength ≥610MPa, yield strength ≥420MPa, and elongation ≥8%, showing broad application prospects in high-load structural components such as aerospace and rail transportation.
[0074] Scale settings instructions
[0075] To better verify the beneficial effects of the present invention, the following comparative examples are provided:
[0076] Comparative Example 1:
[0077] Using the same smelting, refining and casting process as in Example 3, the difference is that no subsequent deformation and heat treatment are performed after casting to obtain a cast Al-Cu-Mg aluminum alloy with added MoAlB.
[0078] The as-cast aluminum alloy obtained in this comparative example was tested for mechanical properties at room temperature. Its hardness was 95HV, tensile strength was 260MPa, yield strength was 185MPa, and elongation after fracture was 5.2%.
[0079] Comparative Example 2:
[0080] Using the same smelting, refining and casting process as in Example 3, the solution was directly subjected to a solution treatment at 490°C for 2 hours and an aging treatment at 165°C for 4 hours, without room temperature rolling, cryogenic treatment and aging treatment.
[0081] The aluminum alloy obtained in this comparative example was tested for mechanical properties at room temperature. Its hardness was 127 HV, tensile strength was 333 MPa, yield strength was 219 MPa, and elongation after fracture was 8.8%.
[0082] Comparative Example 3:
[0083] The same alloy composition and smelting and casting process as in Example 3 were used, the difference being that deep cryogenic treatment was not performed during deformation heat treatment. That is: after solution treatment, a cold rolling was performed at a reduction rate of 50%, followed by pre-aging at 130℃ for 20 min and water quenching, then a second cold rolling was performed at a reduction rate of 60%, and finally, a final aging at 165℃ for 4 h and water quenching.
[0084] The room temperature mechanical properties of the aluminum alloy obtained in this comparative example were predicted. Its hardness was 161HV, tensile strength was 615MPa, yield strength was 435MPa, and elongation after fracture was 8.6%.
[0085] Comparative Example 4:
[0086] The same alloy composition and smelting and casting process as in Example 3 were used, the difference being that pre-aging treatment was not performed in the deformation heat treatment. That is: after solution treatment, 50% cold rolling was performed once, followed by deep cooling with liquid nitrogen for 15 hours to restore to room temperature, and then no pre-aging was performed. The mixture was then directly cold rolled again with a reduction rate of 60%, followed by final aging at 165°C for 4 hours and water quenching.
[0087] The room temperature mechanical properties of the aluminum alloy obtained in this comparative example were predicted. Its hardness was 174HV, tensile strength was 648MPa, yield strength was 450MPa, and elongation after fracture was 7.8%.
[0088] Table 1 shows a comparison of the room temperature tensile properties of Example 3 and Comparative Examples 1-4. As can be seen from the table, after using a multi-stage deformation heat treatment process combining cryogenic treatment and pre-aging, the tensile strength of Example 3 reached 668 MPa, which is significantly higher than that of the comparative examples.
[0089] Table 1. Room temperature mechanical properties of Comparative Examples 1-4 and Example 3
[0090]
Claims
1. A high-strength and high-toughness aluminum alloy strip, characterized in that, The high-strength and high-toughness aluminum alloy strip is composed of Cu 3.8%–4.8%, Mg 1.0%–1.8%, Ti 0.3%–0.5%, Mn 0.2%–0.4%, Mo 0.14%–0.29%, B 0.016%–0.032% by mass, with the balance being Al and unavoidable impurities; the aluminum alloy strip has a hardness ≥165HV, tensile strength ≥610MPa, yield strength ≥420MPa, and elongation ≥8%.
2. A method for preparing the high-strength and high-toughness aluminum alloy strip of claim 1 using MoAlB refinement and deformation heat treatment, characterized in that, The method includes the following steps: S1. MoAlB powder pretreatment: MoAlB powder is dry ball milled to obtain MoAlB powder with a particle size of 2-3 μm. S2. Preparation of Al-coated MoAlB composite powder: Take the MoAlB powder obtained in step S1, and dry it with Al powder by wet ball milling to obtain Al-coated MoAlB composite powder. S3. Melting and casting: Pure aluminum, Al-Cu alloy, Al-Ti alloy and Al-Mn alloy are melted, refined and slag removed, and then Al-coated MoAlB composite powder obtained in step S2 is added. The mixture is stirred and kept warm. Then Al-Mg master alloy is added and cast to obtain aluminum alloy as-cast billet. S4. Deformation Heat Treatment: The aluminum alloy as-cast billet obtained in step S3 is subjected to solution treatment, primary cold rolling, cryogenic treatment, pre-aging, secondary cold rolling, and final aging sequentially to obtain the high-strength and high-toughness aluminum alloy strip. The solution treatment temperature is 480-500℃, with a holding time of 2-3 hours, followed by water quenching. The primary cold rolling employs multi-pass rolling with a total deformation of 40%-50%, and a reduction of ≤10% per pass. The cryogenic treatment medium is liquid nitrogen, held for 12-15 hours, and then restored to room temperature. The pre-aging temperature is 120-140℃, held for 10-20 minutes, and then water quenched. The secondary cold rolling is a multi-pass room temperature rolling with a reduction of 40%-60%. The final aging temperature is 160-170℃, held for 3-6 hours, and then water quenched. In the Al-coated MoAlB composite powder, the amount of MoAlB added is 0.2% to 0.4% of the total mass of the high-strength and tough aluminum alloy strip.
3. The method for preparing high-strength and high-toughness aluminum alloy strip using MoAlB refinement and deformation heat treatment according to claim 2, characterized in that, The dry ball milling in step S1 uses tungsten carbide balls as the grinding medium, with a ball-to-material mass ratio of (8-10):1, a rotation speed of 250-300 rpm, and a milling time of 10-12 h.
4. The method for preparing high-strength and high-toughness aluminum alloy strip using MoAlB refinement and deformation heat treatment according to claim 2, characterized in that, The mass ratio of Al powder to MoAlB powder in step S2 is (2-4):1, the average particle size of Al powder is 10μm; the process control agent for wet ball milling is anhydrous ethanol, the grinding medium is steel balls, the rotation speed is 300-350rpm, and the ball milling time is 8-10h.
5. The method for preparing high-strength and high-toughness aluminum alloy strip using MoAlB refinement and deformation heat treatment according to claim 2, characterized in that, The smelting and casting described in step S3 are as follows: pure aluminum, Al-Cu alloy, Al-Ti alloy and Al-Mn alloy are melted at 740-760℃, slag is removed, Al-coated MoAlB composite powder is added and mechanically stirred for 3-5 minutes and kept at the temperature. The mechanical stirring speed is 250-300 rpm and the stirring is carried out for 3-5 minutes. Then, it is cast at 710-720℃ into a steel mold preheated to 200-300℃.
Citation Information
Patent Citations
Rolling method for ultrahigh-strength aluminum alloy plate
CN106480384A
Metal matrix composite material, preparation method thereof and application of composite material
CN109136611A